Parenting in a 24/7 Economy: Mothers’ Non-standard Work Schedules and Involvement in Children’s Education - Kim, Minseop; Jung, Nahri; Wulandari, Larasati (Frontiers in Psychology, 2022)
Evidence suggests that parental involvement in children’s education has a positive impact on children’s educational achievements and wellbeing outcomes. The trend towards 24/7 economies has obliged many mothers to work nonstandard schedules (i.e., schedules outside traditional daytime, Monday-Friday work schedules). This has raised concerns over how nonstandard work schedules affect parenting behaviors, including paternal involvement in children’s education. Using data from mothers of young children (age 5-6) in Hong Kong (N=433), this study examined the association between maternal work schedules and involvement in children’s home and school activities. The results of structural equation modeling found that weekend work was associated with lower levels of home-based involvement. By contrast, working nonstandard hours was linked with higher levels of school-based involvement. This pattern suggested that nonstandard work schedules could make it either easier or harder for mothers to balance work and family responsibilities, depending on the circumstances (i.e. whether they work nonstandard hours or weekends). Implications and avenues for future research were discussed.